1993
DOI: 10.1159/000177743
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Single Parenteral Application of a 10% Fish Oil Emulsion on Plasma Fatty Acid Pattern and the Function of Thrombocytes in Young Adult Men

Abstract: 50 ml of a 10% fish oil emulsion (41% ω-3 fatty acids of total fatty acids) were infused for 1 h into the arm vein of young, healthy, male volunteers. The fatty acid composition of the plasma, aggregation of the blood platelets as well as the thromboxane synthesis, were measured before the beginning of infusion, 20, 60, 120, 360 and 1,440 min after the start of the fat infusion. In the first 60 min, the fatty acid composition of the plasma changed in correspondence with the supplied fatty acid pattern. At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…This rapid incorporation of ω‐3 PUFAs into phospholipids after a single modest dose is in agreement with the results from 2 small studies in healthy volunteers 39 , 40 . In one study, 50 mL of an FO emulsion similar to the one used in our study was infused for 1 hour 39 . At the end of infusion, plasma fatty acids had changed in correspondence with the supplied fatty acid pattern.…”
Section: Discussionsupporting
confidence: 88%
“…This rapid incorporation of ω‐3 PUFAs into phospholipids after a single modest dose is in agreement with the results from 2 small studies in healthy volunteers 39 , 40 . In one study, 50 mL of an FO emulsion similar to the one used in our study was infused for 1 hour 39 . At the end of infusion, plasma fatty acids had changed in correspondence with the supplied fatty acid pattern.…”
Section: Discussionsupporting
confidence: 88%
“…However, the effects of LEs on coagulation have not been extensively assessed. In one study, platelet aggregation was inhibited immediately following intravenous infusion of a fish-oil-based LE to healthy volunteers, but had returned to normal at 24 h [76]. In surgical patients receiving PN, the latency to collagen-induced platelet aggregation and time to maximal platelet aggregation were significantly longer for a soybean-oil-based LE than for a fish-oil-enriched LE; however, adenosine-diphosphate-induced platelet aggregation and bleeding time were unchanged [77].…”
Section: Evolution Of Parenteral Lipid Emulsionsmentioning
confidence: 99%
“…Data from numerous human studies of parenteral ω‐3 FA supplementation in stressed patients have shown that ω‐3 FAs have a major role in decreasing inflammatory response, 18 , 32 have immunomodulatory effects, 17 , 33 have positive effects on hemostatic parameters, 15 , 34 , 35 reverse preexisting PN‐associated liver disease, 36 and reduce systemic inflammatory response and length of hospital stay in patients undergoing gastrointestinal cancer surgery 16 …”
Section: Discussionmentioning
confidence: 99%
“…It would be valuable to study the effect of ω-3 FAs under conditions of ongoing stress, malperfusion, or impaired lactate clearance. Data from numerous human studies of parenteral ω-3 FA supplementation in stressed patients have shown that ω-3 FAs have a major role in decreasing inflammatory response, 18,32 have immunomodulatory effects, 17,33 have positive effects on hemostatic parameters, 15,34,35 reverse preexisting PN-associated liver disease, 36 and reduce systemic inflammatory response and length of hospital stay in patients undergoing gastrointestinal cancer surgery. 16 Interestingly, a recent study by Bisschop et al 37 demonstrated that major upper gastrointestinal surgery elicits a catabolic response characterized by increased inflammation, glucose production, and protein breakdown.…”
Section: Discussionmentioning
confidence: 99%